Exploring The Supervisor-supervisee Communication Gap: The Case Of Second-year Master Students Of English, University Of 8 May 1945-guelma - Abdaoui, Mounya (جامعة الوادي - University of Eloued, 2021)
The aim of this research paper is to explore the views of second-year Master Students about the supervisor-supervisee communication gap. Many students of English at the University of 8 May, 1945, Guelma were unable to meet the deadline of their Master Dissertation, which is potentially due to supervisors’ late feedback and lack of guidance. To uncover students’ opinions about the problem, a structured questionnaire was administered to 89 Master Students. Quantitative data revealed that 55.05% of them did not meet the deadline although 62.33% of them worked in pairs. In addition, 42.85% of the participants perceived writing dissertations as difficult due to lack of supervisor’s guidance. Furthermore, 53.48% of the informants testified a problem of late response. Interestingly, 60.67% of the respondents insisted that face-to-face meetings remain necessary in the Digital Age. Consequently, the lack of communication can ultimately lead to delay in dissertation completion.
Article
Keywords: Communication; Dissertations; Guidance; Supervisee; Supervisor